Measurement of natural radiation, calculation of radiation doses of agricultural environmental samples in the western region - Kingdom of Saudi Arabia - Roba badghish; Safia Hamidalddin (Journal of Radiation Research and Applied Sciences, 2022)
The activity concentrations of the NORM were measured in thirty samples of plant cultures in agricultural soil irrigated with groundwater from different locations in the Makkah region in Saudi Arabia, using a high purity germanium detector HPGe system. The mean values of the activity concentrations for 226Ra, 232Th, and 40K were found in plants samples 10.41, 1.92, and 4154.92 in Bq. kg−1, for agricultural soil samples were 18.11, 16.12, and 1603.73 Bq. kg−1 respectively, and the irrigation water samples were found 1.57, 0.58, and 118.44 Bq. l−1 respectively. The mean values of Raeq, dose rate, annual effective dose, hazard indices Hex and Hin were 333.09 Bq. kg−1, 179.23 nGy h−1, 1.09 mSv.y−1, 0.89 and 0.92 respectively for plant samples. The gamma doses were higher than world limit values and the Hex and Hin were less unity. The mean values of annual effective doses for ingestion of radionuclides in the plants samples were 2.12 mSv.y−1 for children and 1.86 mSv.y−1 for adults, these results were higher than the world values. These results indicate that, the highest doses refer to the samples location in farm 1, while the lowest values were in farm 3 and farm 6, while the other farms were relatively high than recommended dose values. So, samples of soil, water and plant must be studied in the farm 1 for the highest results of the annual effective doses mSv.y−1 of ingestion of radionuclides in the plants samples for children and adults.